ChemInform Abstract: An Efficient Combinatorial Synthesis of Allocolchicine Analogues via a Triple Cascade Reaction and Their Evaluation as Inhibitors of Insulin Aggregation. Issue 13 (1st April 2014) - Bhowmik, Subhendu; Khanna, Shruti; Srivastava, Kumkum; Hasanain, Mohammad; Sarkar, Jayanta; Verma, Sandeep; Batra, Sanjay
Abstract A total of 21 different analogues is synthesized.